The moderating effect of gender on the relationship between microfinance and the business growth of SMMEs in Gauteng - Msomi, Ncebakazi (University of the Witwatersrand, Johannesburg, 2023)
In a country rife with inequalities and joblessness, Small Medium and Micro Enterprises (SMMEs) have become an alternative means of survival and viable business opportunity for a vast number of South Africans. In order for these SMMEs to operate well, they require capital, which will typically come in the form of microfinance, if at all. The objective of this study was to investigate the impact of the use and cost of microfinance loans on the growth of SMMEs. Furthermore, it was to assess how differently microfinance impacts SMME growth for women compared to when utilised by men. A quantitative research approach was followed to collect the data using an online survey questionnaire. A total of 197 questionnaires were completed butthe analysis was ultimately done on 138 of these, with the exclusion of those with missing values. Data was analysed through the use of Partial Least Squares - Structural Equation Modelling (PLS-SEM). The study found that the costs of microfinance have a significant and negative impact on the growth potential of SMMEs. More specifically, it found that microfinance costs have a more deterring effect on the SMME growth of male owned SMMEs than female owned ones. This study avails a tool and basis for the cost versus benefit analysis that SMMEs must conduct before taking microfinance loans. With women owned SMMEs exhibiting better growth than their male counterparts when using microfinance, an exchange of valuable learnings can occur to improve the country’s SMME success rate. The study proposes innovative systems calibrations and finance product provisions that may benefit both the microfinance institutions and the SMMEs.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management by Research (MMR), Johannesburg 2023
Keywords: Microfinance Loans; Microfinance Costs; Small; Medium and Micro Enterprises; Business Growth; Gender; Women Entrepreneurs; UCTD; SDG-8: Decent work and economic growth